Transformation and precipitation behaviour of Ti–Mo bearing high strength medium-carbon steel. (1st September 2013) - Deng, X; Wang, Z; Misra, R D K; Li, Y; Wang, G
Abstract : The authors describe here the transformation and precipitation behaviour of Ti–Mo bearing high-strength medium-carbon steel during continuous cooling, using a combination of thermo-simulation and microscopy approach. The study demonstrates that Ti and Mo carbides precipitate during austenite-to-ferrite, austenite-to-bainite and even during austenite-to-martensite transformations, contributing to precipitation strengthening. Four different types of precipitates in the size range of 3–200 nm were observed during the transformation. They are spherical (Ti, Mo)C and TiC, cuboidal (Ti, Mo)(C, N) and long thin strips of Fe x C. The size of the precipitates was large and the density was less during austenite transformation. However, the size decreased and density increased during the austenite-to-bainitic ferrite transformation. During the austenite-to-martensite transformation, a high density of fine and spherical-shaped precipitates comprising of Ti and Mo in the range of 3–10 nm were observed.